POTENSI PERUBAHAN MODA TRANSPORTASI KE KAMPUS DENGAN SEPEDA PADA MAHASISWA INSTITUT TEKNOLOGI BANDUNG - Puspa Putri Andani, Fransiska
One of the problems facing big cities today is the problem of congestion and air pollution. The implementation of sustainable transportation system is one of the ways to solve these problems. The sustainable transportation system emphasizes the use of environmentally friendly modes of transport, ie the use of non-motorized transport modes or the use of mass transportation. Bicycles are one of the most ecofriendly modes of transportation and are suitable for use on short-trips. Based on social, economic, and travel characteristics, it is known that most of ITB’s student lives close to the campus, it makes them really potential to use bicycle as their mode of transportation to campus. But not everyone is interested in cycling. This research try to define the group of ITB’s students who potential to substitute their modes of transportation to the campus by bicycle and to know changes in bicycle facilities that can encourage the use of bicycles to campus. The data were obtained through secondary data from PPID ITB and primary data by distributing questionnaires to ITB undergraduate students who live <5 Km from campus. The result shows that the group of students who potentially substitute modes of transportation to the campus by bicycle is a group of students who have no difficulty cycling in heavy traffic, living at a distance of 1-3 Km and have a 1-2 million expenditure. Changes in bicycle facilities needed to encourage bicycle use lead to more secure and convenient bike paths and parking, good lighting, bicycle rental provision and a fairer law for cyclists